MIXTURE DESIGN AND TESTING OF ULTRA HIGH PERFORMANCE FIBER REINFORCED CONCRETE (Malaysian Journal of Civil Engineering, 2018)
This paper describes the mixture formulation process of Ultra High Performance Fiber Reinforced Concrete (UHPFRC). The mixture was developed without using heat treatment, pressure or special mixer. Only ordinary materials available commercially in the Czech Republic were utilized throughout the process. In the first step of the process the cementitious matrix was optimized with respect to its compressive strength and workability. Several types of high-range water reducers (HRWR) and different mixture proportions were tested. In the second step of the optimization process short, high tensile strength steel fibers were added into the matrix that showed highest workability and strength. The compressive strength of the resulting UHPFRC mixtures exceeded 150 MPa after 28 days and the flexural strength in three point bending was in the range of 40 MPa. Such high strengths were achieved due to the utilization of the high strength fibers and low water-to-binder ratio. During the optimization process different amounts of fibers were tested. It was found that with respect to acceptable workability the optimal fiber content is between 2 and 3% by volume.